On Dynamics of Thin Plates with a Periodic Structure - Jędrysiak, J. (Engineering Transactions, 1998)
A new modelling approach to thin elastic Kirchhoff plates with a periodic structure along the midplane based on that given in [7] is shown. The main feature of this model is that it describes the length-scale effect on the plate dynamics, which is neglected in the known asymptotic theories of periodic composite plates. The structural model, which takes into account also the effect of the rotational inertia, and the comparison between this model and the local models without the length-scale effect are presented.